Evaluation of the application of the European guidelines for the diagnosis and clinical care of amyotrophic lateral sclerosis (ALS) patients in six French ALS centres. (1st February 2016) - Marin, B.; Beghi, E.; Vial, C.; Bernard, E.; Lautrette, G.; Clavelou, P.; Guy, N.; Lemasson, G.; Debruxelles, S.; Cintas, P.; Antoine, J. C.; Camdessanche, J. P.; et al.
Abstract : Background and purpose: Our objective was to evaluate the extent to which the 2005 recommendations of the European Federation of Neurological Sciences (EFNS) on the multidisciplinary management of amyotrophic lateral sclerosis (ALS) are followed in clinical practice. Methods: This was a multicentre observational study involving six French ALS referral centres receiving prevalent and incident cases. Recommendations were translated into ad hoc questions referring to key aspects of management, and their application was evaluated by a clinical research assistant who independently examined the medical charts (MCs). When necessary, an independent board‐certified neurologist answered the questions based on examination of the MC and interview of the caring neurologist. Questions regarding diagnosis and communication were put to patients in a self‐administered questionnaire. Results: In all, 376 patients [176 incident, 200 prevalent cases; median age at diagnosis 62.8 years (interquartile range 55.7–72.3); sex ratio 1.37; 27.3% bulbar onset] were included. All the topics covered in the recommendations were evaluated: diagnostic delay (e.g. mean 13.6 months, associated with age and onset); breaking the news (e.g. criteria for communication quality were satisfactory in more than 90%); multidisciplinary and sustained support (e.g. clinic visits were scheduled every 2–3 months in 90%). Also considered were whether riluzole had been offered, symptom management, genetic testing, ventilation, communication defects, enteral nutrition, palliative and end‐of‐life care. Characteristics associated with poor compliance with some guidelines (schedule of visits, delayed riluzole initiation) were also identified. Conclusion: This is the first evaluation of the application of the EFNS recommendations for the management of ALS in a nationwide sample. The results allow us to highlight areas for improvement.